Marine Protected Areas: At the Crossroads of Nature Conservation and Fisheries Management - Kriegl, Michael; Elías Ilosvay, Xochitl E.; von Dorrien, Christian; Oesterwind, Daniel (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) are designated parts of the ocean that restrict human activities to a certain degree. MPAs are established around the world using a wide range of legislative instruments and thus come in a variety of forms and shapes. Despite being regarded as the “cornerstone” of global marine conservation efforts, they currently cover less than 10% of the ocean surface. Individual MPAs aim to achieve goals ranging from the protection of specific habitats or species to sustaining certain commercial activities, such as fishing. By default, the establishment of MPAs intertwines social, ecological and economic considerations. Yet, the emphasis put on each of these domains can vary substantially when setting on-the-ground objectives, frequently creating conflict among stakeholders. In this manuscript, we first discuss current international conservation targets as well as potential future goals and delve into the question of how to assess the effectiveness of MPAs. Subsequently, we discuss the ambivalent role of this widely applied management tool at the crossroads between biodiversity conservation and fisheries management. Placing MPAs in a social-ecological framework, we call for clear and measurable goals to evaluate MPAs from an interdisciplinary perspective. Finally, we present the Baltic Sea, with its high degree of anthropogenic impact, long fishing history and comparatively extensive MPA coverage, as an interesting case study to investigate the role of MPAs in promoting a sustainable management of the ocean.